Pomegranate Extract Enhances Endothelium-Dependent Coronary Relaxation in Isolated Perfused Hearts from Spontaneously Hypertensive Ovariectomized Rats - Delgado, Nathalie T. B.; Rouver, Wender do N.; Freitas-Lima, Leandro C.; de Paula, Tiago D.-C.; Duarte, Andressa; Silva, Josiane F.; Lemos, Virgínia S.; Santos, Alexandre M. C.; Mauad, Helder; Santos, Roger L.; Moysés, Margareth R. (Frontiers in Pharmacology, 2017)
Decline in oestrogen levels promotes endothelial dysfunction and, consequently, the most prevalent cardiovascular diseases in menopausal women. The use of natural therapies such as pomegranate can change these results. Pomegranate (Punica granatum L. (Punicaceae)) is widely used as a phytotherapeutic agent worldwide, including in Brazil. We hypothesized that treatment with pomegranate hydroalcoholic extract would improve coronary vascular reactivity and cardiovascular parameters. At the beginning of treatment, spontaneously hypertensive female rats were divided into Sham and ovariectomized (OVX) groups, which received pomegranate extract (PHE) (250 mg/kg) or filtered water (V) for 30 days by gavage. Systolic blood pressure was measured by tail plethysmography. After euthanasia, the heart was removed and coronary vascular reactivity was assessed by Langendorff retrograde perfusion technique. A dose-response curve for bradykinin was performed, followed by L-NAME inhibition. The protein expression of p-eNOS Ser1177, p-eNOS Thr495, eNOS, p-AKT Ser473, total AKT, SOD-2 and catalase was quantified by Western blotting. The detection of coronary superoxide production was performed using the protocol of dihydroethidium (DHE) staining. Plasma nitrite measurement was analysed by Griess method. Systolic blood pressure increased in both Sham-V and OVX-V groups, whereas it was reduced after treatment in Sham-PHE and OVX-PHE groups. The baseline coronary perfusion pressure was reduced in the Sham-PHE group. The relaxation was significantly higher in the treated group, and L-NAME attenuated the relaxation in all groups. The treatment reduced the p-eNOS (Thr495) in Sham group and prevented the decreasing of p-eNOS (Ser1177) and p-AKT (Ser473) in OVX group. The ovariectomy promoted an increasing in the superoxide anion levels and the treatment was able to prevent this elevation and reducing oxidative stress. We observed a reduction in total cholesterol and LDL in the Sham-PHE group. The treatment with pomegranate hydroalcoholic extract enhances the endothelium-dependent coronary relaxation and improves cardiovascular parameters, which suggests a therapeutic role of pomegranate extract.